Foreign Takeovers and Wages: Theory and Evidence from Hungary - Sándor Csengődi; Rolf Jungnickel; Dieter M. Urban (Hamburg Institute of International Economics (HWWA), 2005)
This study discriminates FDI technology spillover from learning effects. Whenever learning takes time, our model predicts that foreign investors deduct the economic value of learning from wages of inexperienced workers and add it to experienced ones to prevent them from moving to local competitors. Hence, the national wage bill is unaffected by foreign takeovers. In contrast to learning, technology spillover effects occur whenever a worker with MNE experience contributes more to local firms' than to MNEs' productivity. In this case, experienced MNE workers are hired by local firms and the host country obtains a welfare gain. We investigate empirically wages, productivity, and worker turnover during the course of foreign takeovers on employee-employer matched data of Hungary and find evidence consistent with learning, but not with FDI technology spillovers.
Keywords: F2; J3; 330; FDI; foreign takeover; cross-border M&A; wage regression; employeeemployer matched data; propensity score matching; FDI technology spillover; Lohnstruktur; Übernahme; Multinationales Unternehmen; Direktinvestition; Schätzung; Ungarn; picking the winner